Mobile-based protocol-agnostic control over the smart home - Keinestam, Johannes (My University, 2018)
This Master’s thesis describes the development of an interoperability model for allowing control of heterogeneous smart home devices through a single smart home control system. The resulting model is implemented in a mobile application intending to provide reliable and performant device communication. The developed interoperability model allows support for devices to be added to a system implementing the model by writing device drivers which describe a physical device by its metadata and functionality. The functionality of a device is modeled as a list of controls which map the functionality provided by the device to functionality understood by the interoperability model. A control used by a driver must fulfill the contract of one of eight pre-defined controls, thus allowing them to be appropriately rendered in a graphical user interface. The mobile application implementation of the interoperability model uses dynamic code loading to load device drivers written in Lua, for which drivers supporting smart lights from Philips and Plejd are implemented and tested. Evaluation by applying the abstractions of the model to various types of devices finds the model to be highly applicable. However, it is noted that the interoperability model does not support devices which communicate large quantities of binary data such as cameras or media streaming systems. Testing of the implementation further shows that device drivers perform well in a high traffic test environment. The interoperability model is deemed by the author to be relevant to the smart home field through its applicability and ease-of-use, but it is noted that the model should be further tested in real-world environments.
Keywords: Data- och informationsvetenskap; Computer and Information Science